MORALITAS AJARAN ETIS DALAM KONSEP PEMERINTAHAN ISLAM - Suryani, Eli (Alhurriyah, 2015)
One aspect that gets serious attention in the study of classical fiqh siayasat, is the importance of the principle of morality in political theory and practice of Muslims as the caliph of God on earth. Indeed aspect should be inherent moraliatas is paraktek theory of government and state and every country in the world with no notice if the country contains shades of secular government or based on a particular religion. Also by not see whether the state uses the term for the head of state with the term messages caliph, sultan, Malik, kings, and presidents). Urgency value of morality, because they lie in the intrinsic value of human beings depraved. As a framework for implementing a practical rule, almost all literature moral paradigm provides a view of "the nature of government before recognition", that God has chosen party of human groups as a ruler.